Jenis-Jenis Hama Serangga Gaharu (Aquilaria mallacensis Lamk) di Desa Kuapan, Kecamatan Tambang, Kabupaten Kampar, Provinsi RIAU - Sri Rahayu Prastyaningsih; Anna Juliarti (Jurnal Karya Ilmiah Multidisiplin (JURKIM), 2023)
The presence of insect pests has an important effect on the success of plant maintenance. The level of attack caused by insect pests can cause plants to die. The purpose of the study was to analyze agarwood plants that were attacked by insect pests and identify the types of insect pests that attack agarwood plants. The research method used is descriptive. The assessment of the level of damage to agarwood plants due to insect pests is calculated based on the criteria for damage caused by insect pests. Identification of insect pests is carried out directly in the field based on the activity of insects that damage agarwood plants. Based on the results of the identification of insect pests that damage agarwood plants, there are 5 types of insect pests, namely the type of White Flea (Pseudococcus sp.), Leaf Caterpillar (Heortia viitessoides), Pitama hermesalis, Coreidae and Locusta migratoria. The insect pest attack rate is 2.3% and is included in the low category. It is necessary to intensive monitoring can insect pest attacks. If the insect pests found, they should clean up the environment from pests